A descriptive study on the performance of complaints by Turkish university students in an EFL context - Bikmen, Ahmet Süleyman. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The current study investigated the speech act of complaining in Turkish learners of English. The complaints of 100 Turkish learners of English (TLEs) were compared to those of 92 English (ENS) and 108 Turkish native speaker (TNS) participtants, all of whom were students at universities in Turkey and in England. A ten-item discourse completion task (DCT) was used to elicit complaints. The method of analysis involved measuring the frequency of certain complaint strategies. The frequency values for the three groups were compared. Eleven complaint strategies were found in the responses to the DCT. Of these eleven strategies, ‘Hints’ (25%), ‘Requests’ (35%), and ‘annoyance’ (10%) were the most commonly-used. Frequency values obtained for the remaining strategies were all below 8% for all three groups. The ENSs and TNSs (the baseline groups) were found to exhibit significant differences in their frequencies for several strategies. This finding was attributed to the typological differences in pragmatic strategies used by the two languages. The TLEs were then compared to the baseline data. Statistical analysis of the differences in frequencies between the three groups permitted the complaint strategies to be grouped under three headings. These headings are presented with their corresponding strategies in parentheses: Weak Negative Pragmatic Transfer (Modified Blame, Indirect Accusation), No Transfer/ENS-like behavior (Opting Out, Hints, Ill Consequences, Direct Accusations and Threats/Warnings,), and Positive Transfer (Annoyance, Blame [Behavior] and Blame [Person]). Requests did not fit into any of the categories. No examples of Strong Pragmatic Transfer were found in the data. In spite of there being only one instance of Weak Negative Pragmatic Transfer in the statistical findings, a detailed analysis of individual TLE responses led to the conclusion that L1 influence is often present. Complaint frequency was measured in situations where the parameters of power and social distance were controlled for. Compared to the ENS group, the TLE and the TNS groups complained more to authority figures, (power unequal/high social distance contexts) and at lower frequencies to friends (power equal/low social distance contexts) and strangers (power equal / high social distance contexts). One interpretation of the TLEs’ behavior in the authority context is that the TLEs were exhibiting verbosity; that is, offering more explanations, not in an attempt to confront or criticise their superiors, but simply to overcome their real or perceived L2 limitations. Another interpretation is that the TLEs were indeed criticizing their superiors, which might be a dangerous deviation from acceptable norms as characterized by the ENS data obtained in this study.
Keywords: English language -- Study and teaching -- Turkish speakers.; Speech acts (Linguistics)